Status of Flora on Gochang Ungok and Gochang Incheon River Estuarine Protected Wetland Areas - Hyeongcheol Lee; Chang-Su Lee; Sanghun Lee (Geo Data)
Wetland ecosystem is rapidly changing due to human activities and climate change, leading to concerns about biodiversity loss and ecosystem function degradation. Study on the flora of wetlands is essential for conservation and sustainable management. This study analyzes the plant habitats in Gochang Ungok Wetland and Gochang Incheon River Estuary to provide baseline data for wetland protection and management strategies. In Gochang Ungok Wetland, 534 taxa were identified, including endangered two, vulnerable three, and least concern six taxa by Korean red list. Two endangered species and three invasive species were confirmed. In Gochang Incheon River Estuarine Wetland, 400 taxa were identified, including one endangered and three least concern taxa by Korean Red List. Three invasive species were confirmed. The analysis shows that Gochang Ungok Wetland has a higher proportion of wetland plants and greater species diversity compared to Incheon River Estuary. Both wetlands are well-managed, but there is a need to control ornamental and crop species and manage invasive species like common ragweed and bur cucumber. Continuous monitoring and systematic management plans are required to protect valuable species and prevent ecological disturbances.